INTERNATIONAL OIL PRICE AND ITS IMPACT ON THE PERFORMANCE OF IRAQI BALANCE OF PAYMENTS - M. D. Kawther Mohammad Duhaim Hassan (Scholars Digest Publishing, 2023)
The Iraqi economy is one of the rentier economies that has been depend primarily on oil exports, it is known that the price of a barrel of crude oil is a function of a group of economic variables that are experiencing a state of fluctuation and instability in their levels, and these changes mean changes in total revenues and their volatility during short-term, medium-term and long-term periods, this makes the Iraqi economy live in two situations: The first case is fixed obligatory, fixed debts, and variable revenues, so this will lead to a deficit in the balance of payments. The second case is an increase in the deficit. This leads to the inability of the Iraqi government to pay its debts and dues. Therefore, an increase in crude oil prices in the oil markets leads to an increase in crude oil exports. Hence, its revenues increase, and then the demand for imports increases due to the increase in individual incomes, and the rise in prices leads to an increase in the total output, and the opposite occurs in the case of a decrease in the oil price, meaning that its economy is highly affected by price changes in crude oil.
Keywords: oil prices, Iraqi balance of payments, rentier economy and oil exports.